ANALISIS PENGARUH PENDAPATAN ASLI DAERAH, TRANSFER PEMERINTAH PUSAT, DAN SiLPA TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI KALIMANTAN BARAT - Inayah Alainin; Rahma Maulidia; Rusliyawati (Bilancia : Jurnal Ilmiah Akuntansi, 2026)
The objective of this study is to analyze the impact of Local Own-Source Revenue (PAD), Central Government Transfers, and Unspent Budget Surplus (SiLPA) on the financial performance of the West Kalimantan Provincial Government for the years 2021–2025. This study employs a quantitative approach and utilizes secondary data obtained from the Budget Implementation Report (LRA) sourced from the Directorate General of Fiscal Balance (DJPK). Panel data from 14 regencies and cities were analyzed using the Fixed Effects Model (FEM) with EViews 14. The results indicate that local revenue (PAD) has a negative and significant impact on local government financial performance, while central government transfers have a positive and significant impact. SiLPA has a positive but insignificant impact. This study concludes that effective management of local revenue, optimization of central government transfer funds, and improved financial management quality are key factors for local government financial performance.